Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3386/w27891
|View full text |Cite
|
Sign up to set email alerts
|

Face Masks, Public Policies and Slowing the Spread of COVID-19: Evidence from Canada

Abstract: We thank Hiro Kasahara and Kevin Schnepel for excellent comments and suggestions. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w27891.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 3 publications
1
78
1
Order By: Relevance
“…Canada used social distancing, travel restrictions, integration of social sciences as their method. They used well-functioning federalism, long term care, rapid testing and tracing, face mask mandates as their crisis management; partnered with multilayer government [ 77 , 78 , 79 , 80 ].…”
Section: Scientific Review Resultsmentioning
confidence: 99%
“…Canada used social distancing, travel restrictions, integration of social sciences as their method. They used well-functioning federalism, long term care, rapid testing and tracing, face mask mandates as their crisis management; partnered with multilayer government [ 77 , 78 , 79 , 80 ].…”
Section: Scientific Review Resultsmentioning
confidence: 99%
“…This adjustment has the potential to reduce spikes in infections both on campus and at the students’ travel destination, but may come at the cost of harming the mental health of both students and faculty. Next, universities can limit parties and gatherings of large groups, reduce density in dormitories, and require facial coverings which are shown to reduce the spread of infections ( Karaivanov et al., 2020 , Lyu, Wehby, 2020 , Bahl, Eikmeier, Fraser, Junge, Keesing, Nakahata, Wang ). Universities can also choose to cancel sports during the remainder of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A nation-wide study of Canada investigated the impact of mask mandates and other nonpharmaceutical interventions on SARS-CoV-2 growth across 34 public health regions in Ontario, as well as the effect on Canada as a whole at the country level. [ 41 ] The study of Ontario utilized variation in the timing of the adoption of mask mandates in each sub-region, and was conducted over a relatively small geographic area. The study found that within the first few weeks after the mask mandate came into effect, the average weekly number of newly diagnosed SARS-CoV-2 infections decreased by 25–31% in Ontario.…”
Section: Epidemiological Evidence Of Using Face Masks Against Covid-19mentioning
confidence: 99%
“…The study further examined self-reported mask usage, and found that mask mandates increased mask usage by 30%, significantly affecting public behavior towards masking. [ 41 ]…”
Section: Epidemiological Evidence Of Using Face Masks Against Covid-19mentioning
confidence: 99%